Gotti's boys: the Mafia crew that killed for John Gotti - DeStefano, Anthony M. (Citadel Press, 2019)
Profiles the contract killers, fixers, and enforcers whose violent acts of conspiracy, racketeering, extortion, and murder helped John Gotti become the most powerful crime boss in America